Bottleneck Analysis in Garment Production Process Using Simulation Approach (ProModel) - Muchtar, Diki (Sekolah Tinggi Teknologi Wastukancana, 2025)
Garment industry is a labor-intensive manufacturing sector with a complex production flow, highly susceptible to bottlenecks. Unresolved bottlenecks can lead to decreased efficiency, increased waiting times, and reduced productivity. This research aims to analyze bottlenecks in the garment production process using a simulation approach with ProModel software. The research method was carried out using a quantitative-descriptive approach, starting with production system selection, process flow mapping, and simulation model development and testing. The results of the original model simulation show a production output of 1.719 units, with a bottleneck of 3,86% and a cost of USD 38,01. This situation requires improvement, which was achieved through scenario 1, where production capacity at each location was increased, considering a relatively similar cost of USD 41,40. This change reduced the bottleneck to 0,60%, and total production increased to 1.811 units. In scenario 2, with a similar cost, the author recommended further adjustments to the production capacities at the required processes. After conducting the simulation, total production increased to 1.908 units, with a cost of USD 41,42. The simulation using ProModel proved effective in systematically identifying and evaluating bottleneck solutions. This research provides practical recommendations for garment industry management in making data-driven decisions to improve production efficiency. keyword: Bottleneck; Garment Industry; Simulation; ProModel; Production Efficien